If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4v = 4v + 9 Reorder the terms: 9 + 4v = 9 + 4v Add '-9' to each side of the equation. 9 + -9 + 4v = 9 + -9 + 4v Combine like terms: 9 + -9 = 0 0 + 4v = 9 + -9 + 4v 4v = 9 + -9 + 4v Combine like terms: 9 + -9 = 0 4v = 0 + 4v 4v = 4v Add '-4v' to each side of the equation. 4v + -4v = 4v + -4v Combine like terms: 4v + -4v = 0 0 = 4v + -4v Combine like terms: 4v + -4v = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 6(x+3)+8=10x-4(x-5) | | 2(x+8)+8x=10x-16 | | 0-3x=7x-120 | | 5(p+2)=6 | | 6+2(3x-5)=8-5(2x+1) | | 8+3k=3k+8 | | 8(y+1)-5=91 | | -2-4x=9x-106 | | (2i-3)*(5i+1)= | | -6+6c=4c+10 | | log(2x-3)+1=0 | | 2(x+4.9)=23.4 | | -30-6v=-6(6v-5) | | un=3n | | 6x-9w+2y+5w+3x+6y= | | 0.7(x+200)=0.78x-428 | | -3(4-7n)=156 | | 2(k+63)+1=-45 | | 9f+9=9+9f | | -5-7x=-25-11x | | 5t+3=5+5t | | (3x^2+2x-5)+(x^2+6x+8)= | | 6x-9w= | | -2(w+69)=56 | | -221=-5(-6x+1)-3x | | 4(3+4x)-8x=8+2(7x+5) | | 8j=-8+8j | | 6-7x=1-8x | | 1+7p=7+8p | | n-5(3n+1)=7 | | 11x+6=10x+153 | | 4(n-59)-41=35 |